Analisis Penempatan Titik-Titik Rambu Lalu Lintas, di Jalan Lada Ake-Jaya Kota Tidore Kepulauan di Tinjau Dari Aspek Keamanan - Muhammad, Farah Nur; Damayanti, Almiffa; Hi. Muhammad, Amiruddin; Altarans, Indra (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the placement of traffic signs on the Lada Ake–Jaya route in Tidore Islands City from a road user safety perspective. This route is located in a mountainous area with terrain characteristics such as steep inclines, extreme descents, sharp turns, and limited visibility, which have the potential to increase the risk of accidents. Although police data shows no accidents in the past five years, observations and interviews with the public indicate six accident-prone areas that require attention, particularly due to the lack of warning signs, inadequate lighting, and limited visibility on several road segments